"I only relieve myself when I get home in the afternoons": Microaggressions in (queered) bathroom spaces at a South African university. Issue 2 (2nd April 2020) - Brown, Anthony; Maseko, Nonhlanhla; Sedibe, Mabatho
Abstract: This article investigates how lesbian students experience microaggressions in bathrooms at a South African university. We conveniently and purposively used in-depth interviews with 17 lesbian students largely from one of the faculties. Our findings show that notions of microaggression in university bathrooms were not always subtle but pervaded with strong intentions of cissexism and heteronormative messages that had serious implications for the wellbeing of same-sex sexual identity students. Although the university's intent to introduce gender-neutral bathrooms was to address concerns of safety and forceful sexing of the body through the architecture of the traditional gender-binaried bathrooms, lack of engagement with the diverse student populations created confusion and anxiety. In light of the severity of hate crimes towards lesbians in South Africa, participants were of the view that the newly queered bathrooms made them more vulnerable to violence and ostracism. Implications are that the protection and inclusion of people with same-sex sexual identities in university bathroom spaces remain compromised. Tokenistic attempts at gender transformation in institutions of higher learning are indicative of the need for more focused and thought-through approaches with various stakeholders to consider the voices and needs of those directly affected.